2020
DOI: 10.1177/0020764019899975
|View full text |Cite
|
Sign up to set email alerts
|

Dual diagnosis: A systematic review of the organization of community health services

Abstract: Background: Dual diagnosis (DD), as the co-occurrence of a substance use disorder and a psychiatric disorder, is underestimated, under-diagnosed and often poorly treated throughout the world, although it is highly prevalent in people suffering from a mental disorder. Aims and methods: This review analyzed 48 studies from a PubMed and PsycINFO databases search, in order to verify the state of the art regarding the organization of community health services for DD treatment. Results: Four macro-themes have been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 48 publications
1
20
0
1
Order By: Relevance
“…Additionally, telehealth can be used to provide resources for alcohol counseling and addiction treatment, and to follow up closely with patients and give them 24/7 access to care (84). But, according to recent reports (85), a lot of work is needed to support large-scale dissemination and implementation through a multisectoral approach that has the capacity to respond to social needs, mobilize community social capital (8,86), and provide training to social and health care providers on substance use and mental health disorders (8). These approaches can reduce health, economic and social inequity (87) that exacerbate mental illness (7) and alcohol consumption (88).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, telehealth can be used to provide resources for alcohol counseling and addiction treatment, and to follow up closely with patients and give them 24/7 access to care (84). But, according to recent reports (85), a lot of work is needed to support large-scale dissemination and implementation through a multisectoral approach that has the capacity to respond to social needs, mobilize community social capital (8,86), and provide training to social and health care providers on substance use and mental health disorders (8). These approaches can reduce health, economic and social inequity (87) that exacerbate mental illness (7) and alcohol consumption (88).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, this clinical indication contributes to avoid the use of illicit substances, because patients are placed in a protected context, away from the pathological environment; on the other hand, it allows to follow specific psychological and pharmacological therapeutic strategies, aimed at maintaining the mood stabilization and correcting the unhealthy lifestyles for a better social and familial functioning. Thus, the high rates of comorbidity between severe mental illness and SUD need an integrated approach in psychiatric services with specialized clinicians to encourage early assessment and intervention with active and careful monitoring ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of problems in families is not new. Clearly, the significant developments associated with dual diagnosis provide an example of the extensive work required to bring practice frameworks and organizations together, although a recent meta‐analysis showed that, in spite of years of work, this practice remains contentious (Fantuzzi & Mezzina, 2020). Similar extensive work has not yet occurred with domestic violence.…”
Section: Literature Reviewmentioning
confidence: 99%